Bilateral preventive mastectomy as a preventive method of breast cancer in the opinion of women - Olejniczak-Nowakowska, Małgorzata; Trocha, Weronika; Krupa-Kotara, Karolina; Grajek, Mateusz (Quality in Sport, 2023)
Background Breast cancer is the most common cancer among women. Despite of the progress of medicine and develop of treatment, it is still the second couse of death among women. To reduce the risk of getting breast cancer, the more ofen teratement is "preventive mastectomies" which completely remove the breast gland by healty women that are in the "high risk" group. Material and Methods To conduct the research I develop a survey, written by my own. The study included 252 women from Poland over the age of 18. Results The opinion about the performance of preventive mastectomies in case of women in "high risk" was very diverse. Only 13% of interviewees were convinced that they would have the surgery and up to 29% could not give an answer. Most woman (86%) are convinced that breast cancer is genetically determined. That mastectomy can be a way to prevent breast cancer agrees 69% of respondents. More than half of respondents (52%) don't know if such surgery is in Poland available. Only half of the respondents could indicate the place where an examination of an increased risk of breast cancer can be made (49%). 81% of respondents examine there breasts at least with one method, and 19% did not check it at all. Conclusions The knowledge about the heredity of cancer and the availability of treatments is insufficient. Women are not convinced that they would have gone to radical preventive treatment, and they are afraid of many consequences connected with it. It is essential to educate the public including the medical stuff in this scope. It is also important that the patient together with his doctor examined all the possible options for limiting the risk of cancer.